TRENDS IN MAJOR RUMINANT MEATS PRODUCTION AND THE ROLES OF THE MACROECONOMIC ENVIRONMENT IN NIGERIA - Sunday Brownson AKPAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study analyzed the trends in major ruminant meats (beef, chevon, mutton, and total ruminant meat) and provided empirical evidence on the relationship between ruminant meats production and key macroeconomics fundamentals in Nigeria. The study employed the time-series data that were sourced from the Food and Agricultural Organization (FAO), Central Bank of Nigeria,and the World Bank and ranging from 1961 to 2021. The descriptive analyses, trend equation, and multivariate autoregressive model were used to analyze the data. The result of the data analyses revealed an annual exponential growth rate of 1.156%, 6.694%, 6.032%, and 2.747% for beef, chevon, mutton, and total ruminant meat respectively. The empirical outcomes showed that the annual inflation rate has a significant negative inelastic association with the ruminant meats production in Nigeria; while the per capita income had a significant positive inelastic relationship. Moreover, the annual nominal exchange rate exhibited a mixed effect on ruminant meat production. To improve ruminant meat production in the country, it is strongly suggested that the inflation rate should be moderated and the country should develop sound and efficient policies to increase the per capita income.